Creating new values for children’s luggage using Kansei Engineering methodology - Wang, Mingrun; Shaari, Nazlina; Yan, He (Springer, 2020)
The popularity of parent-child travel cannot drive the sales of children’s luggage well. This is because the design of current children’s luggage cannot satisfy the expectations of parents. Products with novelty and versatility are more likely to appeal to consumers and meet consumers’ needs in pursuit of high quality of life. Therefore, new values need to be created for children’s luggage to increase its competitive advantage. However, the methods for creating values for a new product are still lacking. To support the sales of children’s luggage and its industrial development, this study aims to show the way the Kansei Engineering methodology targets children’s luggage to create new values in a new perspective. A total number of 26 new values of children’s luggage were selected for evaluation. The framework of creating values for new children’s luggage in this study can improve the attractiveness of a product. Consequently, the children’s luggage as well as other kinds of products that are facing elimination can have a chance of development.